Pengaruh Pemasangan Bidai Dengan Tingkat Nyeri Pada Pasien Di RSUD Kabupaten Karo: Effect of Splinting on Pain Levels in Patients at Karo Regency Regional Hospital - Saragih, Hartaulina; Widyowati, Agustin; Ana Anggraini, Novita; Indasah (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Trauma resulting from accidents causing bone fractures remains a significant health issue in many countries, both developed and developing. Fractures, especially in the lower and upper extremities, are common outcomes of such incidents. In Indonesia, femur fractures are the most prevalent, with traffic accidents being a primary cause. This study aimed to assess the impact of proper splint application on reducing pain levels in patients at the Karo District General Hospital. The study involved evaluating the knowledge and skills of healthcare workers in applying splints, focusing on pain reduction outcomes. The assessment revealed that the application of splints at Karo District General Hospital had a pain reduction success rate of 49%. The primary issue identified was the insufficient knowledge and skills of healthcare workers in properly applying splints to minimize patient pain. To improve the effectiveness of splint application in reducing pain, training for healthcare workers is essential. Providing this training will enhance their knowledge and skills in using the appropriate splinting techniques for pain management in trauma patients.